Testing the Views of Children of Terrorists: A Comparative Analysis with Children from Low-Income Families - Harahap, Husnul Isa (SCAD Independent, 2020)
This research was carried out in the Pondok Pesantren Al-Hidayah. This pesantren is located in Deli Serdang District, North Sumatra Province, Indonesia. It is a boarding school that educates children of terrorists and low-income families. This study aimed to analyze the differences between children of terrorists in comparison to children from low-income families, from the perspective of Indonesian nationalism. The subject is Pancasila: the official, foundational philosophical theory of the Indonesian state. The findings of this study indicated that children from low-income families had a better understanding of Pancasila than children of terrorists. However, this does not mean that all children of terrorists did not understand Pancasila, as there were still those who did comprehend a small amount. Regarding the tendency for violence, this study had found that both children of terrorists and children from low-income families both had a desire to hit if bullied or ridiculed. One prominent difference is that children of terrorists seemed to have different imaginations. They might have visions of heaven as well as sharp objects. The percentage of this occurrence was minuscule, which means this trend did not occur in all children of terrorists. However, this finding indicated that children of terrorists needed special attention.